2019
DOI: 10.1186/s12891-019-2609-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the RANK/RANKL/OPG system in the human intervertebral disc: implication for the pathogenesis of intervertebral disc degeneration

Abstract: Background The expression of the receptor activator of nuclear factor kappa B (RANK) /RANK ligand (RANKL) /osteoprotegerin (OPG) system and its association with the progression of intervertebral disc (IVD) degeneration has recently been reported in a human IVD. However, the effect of the RANK/RANKL/OPG system on the matrix metabolism of human IVD cells, especially on the expression of catabolic factors relevant to IVD degeneration, remains unknown. The purpose of this study was to examine the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
(58 reference statements)
3
17
1
Order By: Relevance
“…Receptor activator of nuclear factor-kappa B (RANK) and its ligand RANKL and the decoy receptor osteoprotegerin (OPG) are central regulators of osteoclast development and essential for osteoimmunology [9][10][11][12]. Recent study showed that RANKL/OPG ratio was significantly increased in the gingival tissues surrounding mini-implants in the rat model with Porphyromonas gingivalis LPS inductions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Receptor activator of nuclear factor-kappa B (RANK) and its ligand RANKL and the decoy receptor osteoprotegerin (OPG) are central regulators of osteoclast development and essential for osteoimmunology [9][10][11][12]. Recent study showed that RANKL/OPG ratio was significantly increased in the gingival tissues surrounding mini-implants in the rat model with Porphyromonas gingivalis LPS inductions [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, receptor activator of NF-κB ligand (RANKL) is a member of the tumor necrosis factor ligand superfamily, and it is known that RANKL, its signaling receptor (RANK), and its decoy receptor osteoprotegerin (OPG) are key regulators of the production of extracellular matrix remodeling enzymes [10]. Recently, the expression level of the RANK/RANKL/OPG system was found to be upregulated in degenerated human IVD tissues and be associated with in the process of IVD degeneration [11]. More importantly, the upregulation of RANK/RANKL/OPG can result in the biosynthesis of extracellular matrix-degrading enzymes, including matrix metalloprotease-3 (MMP-3) and MMP-13 in degenerated IVD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the expression level of the RANK/RANKL/OPG system was found to be upregulated in degenerated human IVD tissues and be associated with in the process of IVD degeneration [11]. More importantly, the upregulation of RANK/RANKL/OPG can result in the biosynthesis of extracellular matrix-degrading enzymes, including matrix metalloprotease-3 (MMP-3) and MMP-13 in degenerated IVD [11]. On the other hand, neurotrophin is another biological contributor for the progression of IVD degeneration [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations